The Development and Initial Validation of the REST Questionnaire: A Multidimensional Tool for Assessing Fatigue in Individuals with and Without a History of Cancer - Giuseppe Di Lorenzo; Carlo Buonerba; Raffaele Baio; Eleonora Monteleone; Francesco Passaro; Antonio Tufano; Vittorino Montanaro; Vittorio Riccio; Ilaria Gallo; Francesca Cappuccio; Federica Fortino; Anna Buonocore; et al. (Diseases)
Background: Fatigue is a prevalent and complex condition with significant impacts on well-being. Existing fatigue assessments often lack comprehensiveness or practicality for general population studies. Methods: This study validated the REST Questionnaire, a novel fatigue assessment tool, in a sample of 268 adults. Psychometric properties, including internal consistency and construct validity, were evaluated. REST scores were correlated with WHO-5 well-being, BMI, self-rated health, and chronic conditions. Exploratory factor analysis identified underlying dimensions of fatigue. Results: The REST Questionnaire demonstrated excellent internal consistency (Cronbach’s alpha = 0.918) and construct validity. Higher fatigue scores were associated with lower well-being, female gender, and the presence of certain chronic conditions (cancer, kidney stones, gastric ulcers). Two distinct fatigue dimensions, “physical fatigue and functional impacts” and “emotional and social consequences”, were identified. Conclusions: The REST Questionnaire is a reliable and valid tool for assessing fatigue in the general population. Its multidimensional framework and sensitivity to comorbidities offer valuable insights for research and public health applications, with the potential to inform targeted interventions aimed at improving well-being.